Bovine serum albumin binding, antioxidant and anticancer properties of an oxidovanadium(IV) complex with luteolin - Naso, Luciana Gissella (2016)
Chemotherapy using metal coordination compounds for cancer treatment is the work of the ongoing research.Continuing our research on the improvement of the anticancer activity of natural flavonoids by metal complexation,a coordination compound of the natural antioxidant flavone luteolin (lut) and the oxidovanadium(IV) cationhas been synthesized and characterized. Using different physicochemical measurements some structural aspects of [VO(lut)(H2O)2]Na·3H2O (VOlut) were determined. The metal coordinated to two cis-deprotonated oxygen atoms (ArO−) of the ligand and two H2O molecules. Magnetic measurements in solid state indicatedthe presence of an effective exchange pathway between adjacent vanadiumions. VOlut improved the antioxidant capacity of luteolin only against hydroxyl radical. The antitumoral effects were evaluated on MDAMB231 breastcancer and A549 lung cancer cell lines. VOlut exhibited higher viability inhibition (IC50=17 μM) than the ligand on MDAMB231 cells but they have the same behavior on A549 cells (ca. IC50=60 μM). At least oxidative stressprocesses were active during cancer cell-killing. When metals chelated through the carbonyl group and one adjacent OH group of the flavonoid an effective improvement of the biological properties has been observed. In VOlut the different coordination may be the cause of the small improvement of some of the tested properties of the flavonoid. Luteolin and VOlut could be distributed and transported in vivo. Luteolin interacted in the microenvironment of the tryptophan group of the serum binding protein, BSA, by means of electrostatic forces and its complex bind the protein by H bonding and van derWaals interactions.